CLINICAL AND HAEMATO-BIOCHEMICAL STATUS FOLLOWING CRYSTALLOID AND COLLOID FLUID THERAPY IN DYSTOCIA AFFECTED BUFFALO SUBJECTED TO OBSTETRICAL MANEUVERING - RAJAT,; GHUMAN, S P S; CHEEMA, R S; SINGH, N (The Indian Journal of Animal Reproduction, 2016)
The impact of crystalloid (Normal or Hypertonic saline) and colloid (Dextran-40 or Polygeline) based fluid therapies on clinical and haemato-biochemical status as well as survival rate of 24 dystocia-affected buffalo subjected to obstetrical maneuvering was assessed. Depending upon fluid therapy administered, the buffalo were divided (n=6 each) into groups namely, group NSS (Normal saline solution 5-10 L, i.v.), group H+O (7.2% Hypertonic saline solution, HSS @ 4 ml/kg b wt, i.v. + Oral fluid/freshwater @ 40 ml/kg b wt), group D+H+O (Dextran-40 @ 20 ml/kg b wt, i.v. + HSS + Oral fluid) and group P+H+O (Polygeline @ 20 ml/kg b wt, i.v. + HSS + Oral fluid). Blood samples following delivery of fetus were collected immediately before the start (0 h) and at 6, 12 and 24 h after the start of fluid therapy. Heart rate decreased (p
Keywords: Buffalo; Dystocia; Fluid therapy; Haemato-biochemical; Obstetrics